IQLIM O‘ZGARISHI OQIBATIDA INSONLARDA YANGI EPIDEMIYA VA BAKTERIYALARNING TARQALISHI (UBS Scientific Bulletin, 2025)
In the article, it is no secret that global climate change, which willcause new epidemics and global population of bacteria, is the most urgent issue  today, because the atmosphere is filled with various harmful gases and dust. Itcaused a number of other problems as a result of its sudden change and its seriousimpact on human health, the population suffers from various diseases caused byharmful epidemics and bacteria, and the quality of agricultural crops deteriorates.It is intended to understand the effects of climate change, assess its dangerousconsequences, prevent it, introduce and implement measures to adapt to theconditions of climate change in Uzbekistan to the population and students, and thehealth of the population is in their own hands. it is intended to explain to them thatit is.